Peak velocity and its time limit are as good as the velocity associated with VO2max for training prescription in runners - Manoel, Francisco de Assis; da Silva, Danilo F.; Lima, Jorge Roberto Perrout de; Machado, Fabiana Andrade (Sports Medicine International Open, 2017)
This study compared the effects of 4 weeks of training prescribed by peak velocity (Vpeak) or velocity associated with maximum oxygen uptake (vVO2max) in moderately trained endurance runners. Study participants were 14 runners (18–35 years) randomized into 2 groups, named group VO2 (GVO2) and group Vpeak (GVP). The GVO2 had training prescribed by vVO2max and its time limit (tlim), whereas the GVP had training prescribed by Vpeak and its tlim. Four tests were performed on a treadmill: 2 maximum incremental for Vpeak and vVO2max and 2 for their tlim. Performance (10 km) was evaluated on a 400 m track. Evaluations were repeated after 4 weeks of endurance training. The results showed a significant effect of training on Vpeak [GVP (16.7±1.2–17.6±1.5 km.h−1), GVO2 (17.1±1.9–17.7±1.6 km·h−1)]; vVO2max [GVP (16.4±1.4–17.0±1.3 km·h−1), GVO2 (17.2±1.7–17.5±1.9 km·h−1)]; and 10 km performance [GVP (41.3±2.4–39.9±2.7 min), GVO2 (40.1±3.4–39.2±2.9 min)]. The Vpeak highly correlated with performance in both pre- and post-training in GVP (–0.97;–0.86) and GVO2 (–0.95;–0.94), as well as with vVO2max in GVP (–0.82;–0.88) and GVO2 (–0.99; –0.98). It is concluded that training prescribed by Vpeak promoted similar improvements compared to training prescribed by vVO2max. The use of Vpeak is recommended due to its practical application and the low cost of determination.
Keywords: training programs; effort testing; athletic performance; running